SISTEM APLIKASI KEHADIRAN STAFF DESA BERBASIS WEB DENGAN MENGGUNAKAN PHP DAN MYSQL: STUDI DESA BESILAM KECAMATAN PADANG TUALANG - Eka Putra; Rizky Vita Losi; Sutan Putra Nauli Harahap (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2023)
This research aims to design a website-based staff attendance application system using PHP and MySQL. This research was conducted at the Besilam Village Office, Padang Tualang District. This research uses qualitative methods with observational data collection techniques and literature studies. The process of storing attendance data for Besilam village staff still uses manual methods. Data storage like this can lead to insecure data. Therefore, researchers will create a computerized village staff attendance application system that is quite adequate web-based where php as the programming language and mysql xampp as the database. From the problems that have been obtained so that researchers can get a solution to their handling by implementing a web-based application for the presence of Besilam village staff. It can be concluded that the application made by researchers can help the village process staff attendance data quickly and safely